Using the design for Six Sigma approach with TRIZ for new product development. (August 2016) - Wang, Fu-Kwun; Yeh, Ching-Tan; Chu, Tao-Peng
Highlights: The DFSS with TRIZ method is used to develop a new product. We present a case study to demonstrate how the DMADV framework with TRIZ is used to develop a new network device. The profit of this 4-year study is US$6, 555, 262. Seven patents are invented during this product development. Abstract: Design for Six Sigma (DFSS) is a proactive process that entails incorporating the voices of customers into the design of products and processes. DFSS is used to establish a quality design by implementing preventive thinking and tools in the product development process. Recently, an innovative theory of inventive problem-solving (TRIZ) approach has been successfully incorporated into product development processes. In this paper, we present a case study conducted based on the DFSS with TRIZ method for developing a new product called very-high-bit-rate digital subscriber line 2 comprising multiple-dwelling units. The results indicate that the DFSS with TRIZ method can be effectively applied in new product development. The profit of this 4-year study is projected at US$6, 555, 262. Seven patents are invented during this product development.